Stress granules as RNA triage hubs suppress extracellular vesicle secretion under oxidative stress in cancer - Yue Dong; Takeshi Yoshida; Mitsuyo Maeda; Haruki Adachi; Asami Eguchi; Emi Mishiro-Sato; Daisuke Okuzaki; Yosky Kataoka; Takuya Yoshida; Chitose Oneyama (Proceedings of the National Academy of Sciences, 2026)
Cancer cells confronting oxidative stress must coordinate their extracellular vesicle (EV) secretion to balance intercellular signaling with the intracellular programs required for survival, yet how these decisions are integrated remains poorly understood. Here, we identify a stress-adaptive mechanism in which stress granules (SGs) selectively suppress CD63 + EV release. Using a bioluminescent EV–reporter screen, we found that the clinical compound YM155 selectively inhibits CD63 + EV secretion across diverse tumor cells. Mechanistically, YM155 rapidly inactivates the antioxidant transcription factor FOXO3a, diminishing expression of key detoxifying enzymes and leading to delayed but sustained accumulation of reactive oxygen species (ROS). Elevated ROS drives SG formation, and these SGs function not as passive storage sites but as RNA triage hubs that exclude and destabilize a subset of transcripts. Among them, Rab27A mRNA—encoding a GTPase essential for multivesicular-body docking to the plasma membrane—is selectively excluded and degraded, resulting in loss of Rab27A protein and suppression of CD63 + EV secretion. Forced Rab27A expression restores EV release but paradoxically reduces proliferation under oxidative stress, indicating that EV suppression is prosurvival. The same FOXO3a–ROS–SG–Rab27A axis operates during physiological glucose deprivation and is evident in vivo, where SGs form in xenograft tumors and circulating CD63 + EVs decline. Pancancer transcriptomic analyses further show that Rab27A expression correlates with FOXO3a-dependent antioxidant programs, underscoring clinical relevance. These findings reveal that SGs actively reprogram RNA fate to tune vesicle output, establishing a redox-responsive mechanism by which cancer cells transiently suppress EV secretion to enhance survival.